Answer:
10
Step-by-step explanation:
g(f(x)) = g(3x² - 4) = 2(3x² - 4) - 6
so
g(f(2) = 2(3*2² - 4) - 6 = 2*8 - 6 = 16 - 6 = 10
The required value of y is 2645 / 77 when x = 77.
Step-by-step explanation:
1. Let's check the information given to answer:
if y varies inversely as x, and y = 23 when x = 115. Find y when x=77
2. What is y when x = 77?
As the statement "y varies inversely as x" translates into y = k/x
If we let y = 23 and x = 115, the constant of variation becomes
23 = k ÷ 115
k = 23 × 115
k = 2645
Thus the specification equation is y = 2645 ÷ x . Now, letting x = 77, we obtain
y = 2645 ÷ x
y = 2645 ÷ 77
<u>So, The required value of y = 2645 / 77 when x = 77</u>
<u></u>
<u>#learnwithBrainly</u>
Answer:
By making ‘a’ the subject, I believe you mean isolate the variable ‘a’.
1/a - 1/b = 1/c : add 1/b to both sides
1/a = 1/b + 1/c : combine the unlike fractions by finding a common denominator, bc is the common denominator
1/a = (1/b)(c/c) + (1/c)(b/b) : simplify
1/a = (c/bc) + (b/bc) : add numerators only, because the denominators match
1/a = (c + b)/bc : multiply both sides by a
1 = (a)[(c + b)/bc] : multiply both sides by the reciprocal of [(c + b)/bc] which is [bc/(b + c)]
1[bc/(b + c)] = a
a = bc/(b + c)
This will not work if c = -b, because then you would be dividing by zero.
Example: 1/2 - 1/3 = 1/6 a = 2, b = 3 c= 6
a = bc/(b + c) => 2 = (3 x 6)/(3 + 6) => 2 = 18/9 => 2 = 2.
Step-by-step explanation: